Structuring ampelographic collections by phenotypic characteristics and comparing the reaction of grape varieties to climate change - L. Yu. Novikova; L. G. Naumova (Вавиловский журнал генетики и селекции)
Modern climate changes task breeders to adapt viticulture to the new natural resource potential of the regions. A necessary condition is the assessment and analysis of current trends in changing the characteristics of contrasting groups of varieties. The aim of the study is to identify homogeneous groups  of varieties of an ampelographic collection and to compare the rates of reaction  of their agrobiological parameters to climate changes. Material for the study consists of observations of 21 agrobiological characteristics of 109 grape varieties from the Don ampelographic collection named after Ya.I. Potapenko (Novocherkassk) with an observation period from 10 to 36 years in 1981–2017. The sample included  Vitis vinifera L. varieties and the V. vinifera L. × V. labrusca L. and V. vinifera L. × V. amurensis Rupr. interspecific hybrids, and hybrids from crosses between V. vinifera L. and several American species. Homogeneous groups  of characteristics and varieties are identified by principal component analysis (PCA) and analysis of variance (ANOVA) methods. Trends in changing the agrobiological characteristics of the varieties and groups  of varieties are calculated.  PCA revealed  that the main differentiating factor of the studied fragment of the ampelographic collection is the size of the bunch; the second, the yield; the third, the time of ripening. The values of the factors are contrasting in varieties of different  directions  of use and taxonomic origin, which was confirmed  by ANOVA. The groups  of the V. vinifera × V. labrusca and V. vinifera × V. amurensis hybrids do not differ significantly from each  other  in most  indicators,  exceeding V. vinifera varieties in the  number of elements of productivity, winter hardiness and yield. Complex hybrids with American species have an intermediate position  between these  groups exceeding all groups  in bunch  weight.  All groups  of cultivars show trends  towards  a reduction in productive period,  an increase  in the mass of bunch  and yield, sugar content and a decrease in acidity. The V. vinifera × V. labrusca hybrids are distinguished by the highest growth  rate of the bunch  mass caused  by a reduction in the duration of active growth  and a decrease in the percentage of fruit-bearing shoots.  A higher  reduction rate of the production period  and a decrease in acidity were observed in later varieties. Regression analysis showed that the acceleration of the ripening of grapes is largely due to rising temperatures.